KARAKTERISASI NANOPARTIKEL KITOSAN EKSTRAK DAUN UBIJALAR (Ipomoea batatas L.) MENGGUNAKAN METODE GELASI IONIK - Ade Indriani Putri; Agus Sundaryono; I Nyoman Chandra (ALOTROP, 2018)
The purpose of this study is to determine and measure the results of the characterization of Chitosan nanoparticle synthetized from leaves of sweet potato (Ipomoea batatas l.) extracts . The methods used to make nanoparticles is made with Ionic Gelation method based on electrostatic interaction between the Hydroxyl Amine on Chitosan with cluster of negative charge from the polianion NaTPP with conditioned surfactant Tween 80 used as surfactant. Characterization test of nanoparticle morphology in this study obtained using the Fourier Transformation  Infra Red (FTIR), and Particle Size Analyzer (PSA). Results with FTIR characterization test from the obtained Chitosan-white purple sweet potato leaf extract nanoparticles has a cluster of N-H and P = O that show the occurrence of ammonium ion interaction between Chitosan with polianion from NaTPP and sweet potato leaves. The interaction seen from wave number and intensities  O-H shifting from pure Chitosan at 3425.56 cm-1 to 3427, 51 cm-1, as well as on pure Chitosan N-H absorption  undergoes a shift from 1597, 06 cm-1 to becomes 1629.85-1 cm-1, which shows that there has been a cross connective between ammonium ion on Chitosan and Posphat from NaTPP and white purple sweet potato leaf extract. The results of the analysis from the PSA, is known to the average Nanokitosan particle sizes extracts from white purple sweet potato leaf extracts with the addition of NaTPP i.e. of 302.6 nm and that the aim of the research on Chitosan nanoparticle synthesis has been successfully done.